Control of respiration in fish, amphibians and reptiles - Taylor, E.W.; Leite, C.A.C. [UNESP]; McKenzie, D.J.; Wang, T. (Associação Brasileira de Divulgação Científica (ABRADIC), 2010)
Fish and amphibians utilise a suction/force pump to ventilate gills or lungs, with the respiratory muscles innervated by cranial nerves, while reptiles have a thoracic, aspiratory pump innervated by spinal nerves. However, fish can recruit a hypobranchial pump for active jaw occlusion during hypoxia, using feeding muscles innervated by anterior spinal nerves. This same pump is used to ventilate the air-breathing organ in air-breathing fishes. Some reptiles retain a buccal force pump for use during hypoxia or exercise. All vertebrates have respiratory rhythm generators (RRG) located in the brainstem. In cyclostomes and possibly jawed fishes, this may comprise elements of the trigeminal nucleus, though in the latter group RRG neurons have been located in the reticular formation. In air-breathing fishes and amphibians, there may be separate RRG for gill and lung ventilation. There is some evidence for multiple RRG in reptiles. Both amphibians and reptiles show episodic breathing patterns that may be centrally generated, though they do respond to changes in oxygen supply. Fish and larval amphibians have chemoreceptors sensitive to oxygen partial pressure located on the gills. Hypoxia induces increased ventilation and a reflex bradycardia and may trigger aquatic surface respiration or air-breathing, though these latter activities also respond to behavioural cues. Adult amphibians and reptiles have peripheral chemoreceptors located on the carotid arteries and central chemoreceptors sensitive to blood carbon dioxide levels. Lung perfusion may be regulated by cardiac shunting and lung ventilation stimulates lung stretch receptors.
Keywords: Vertebrates; Control of respiration; Respiratory rhythm generation; Water and air breathing; Chemoreceptors; Mechanoreceptors